2019
DOI: 10.18805/lr-500
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Mapping of a Soybean Glabrous Gene Using Specific-Locus Amplified Fragment Sequencing Method

Abstract: Trichome is a natural trait related with plant defense and seed yield, however, the genetic control of this trait has not been extensively studied in soybean. In this study, a cross was made between a soybean landrace “Aijiaomaodou” with normal pubescence and a glabrous soybean line “39002”. The segregation ratio of the F2 population was fit to the expected value and the glabrous phenotype was controlled by a single dominant gene. Association analysis was conducted to identify candidate genes for the glabrous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The frequent usage of limited elite lines may lead to a relatively narrowed genetic background of vegetable soybean [ 20 , 21 ]. The development of related markers and the mining of specific genes can provide marker resources for molecular-marker-assisted breeding and further reveal the genome composition of the two soybean types [ 27 , 28 ]. This will have an important guiding significance for the classification of vegetable soybean breeding, and can effectively improve the directivity of vegetable soybean breeding and promote the development of the vegetable soybean industry.…”
Section: Discussionmentioning
confidence: 99%
“…The frequent usage of limited elite lines may lead to a relatively narrowed genetic background of vegetable soybean [ 20 , 21 ]. The development of related markers and the mining of specific genes can provide marker resources for molecular-marker-assisted breeding and further reveal the genome composition of the two soybean types [ 27 , 28 ]. This will have an important guiding significance for the classification of vegetable soybean breeding, and can effectively improve the directivity of vegetable soybean breeding and promote the development of the vegetable soybean industry.…”
Section: Discussionmentioning
confidence: 99%
“…Gene mapping using genome-wide SNPs markers generated by polymorphic specific-locus amplified fragments identified the 2.76-Mb genome region (47,315,610–50,072,564) on chromosome 9 containing 551 candidate genes associated with the glabrous trait. Four genes including Glyma09G280500 , Glyma09G282600 , Glyma09G259400 , and Glyma09G283400 in the region appeared to be the most important candidate genes that are highly related to the glabrous trait [ 116 ].…”
Section: Technological Interventions To Address the Constraintsmentioning
confidence: 99%
“…Recently, Yu et al (2020) also worked out genetic of hairy trait in a cross between soybean landrace 'Aijiaomaodou' with normal pubescence and a glabrous soybean line '39002' and reported that glabrous genotypes was controlled by single dominant gene. They also extend their study to identify genomic location of glabrous (P1) gene that was mapped to the chromosome 9 with an interval of 2.76 Mb.…”
Section: Inheritance Of Glabrous Traitmentioning
confidence: 99%
“…Furthermore, Bernard and Singh (1969) reported considerable variation among varieties of soybeans with respect to size, shape, durability and distribution of plant hairs including P1 (glabrous), pc (curly pubescence), Pd (dense pubescence), Ps (sparse pubescence) and p2 (puberulent). Research has shown that each of the five types differed from the normal by a single gene pair and that the five loci separated independently (Yu et al 2020). Developing dark-green unblemished green pods preferably with no (glabrous pods) or sparse grey pubescence is one of the major breeding objectives in vegetable soybean.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation